2016
DOI: 10.1113/jp271826
|View full text |Cite
|
Sign up to set email alerts
|

Bassoon and piccolo regulate ubiquitination and link presynaptic molecular dynamics with activity‐regulated gene expression

Abstract: Release of neurotransmitter is executed by complex multiprotein machinery, which is assembled around the presynaptic cytomatrix at the active zone. One well-established function of this proteinaceous scaffold is the spatial organization of synaptic vesicle cluster, the protein complexes that execute membrane fusion and compensatory endocytosis, and the transmembrane molecules important for alignment of pre- and postsynaptic structures. The presynaptic cytomatrix proteins function also in processes other than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…One of the highly conserved AZ components is the large (Ͼ500 kDa) scaffold protein Piccolo, which organizes various aspects of presynaptic function at chemical synapses (Cases-Langhoff et al, 1996;Wang et al, 1999;Gundelfinger et al, 2016). Among these are functions in AZ assembly during synaptogenesis (Shapira et al, 2003), the dynamic regulation of presynaptic actin (Waites et al, 2011;Wagh et al, 2015), the control of presynaptic proteostasis (Waites et al, 2013;Ivanova et al, 2016), the regulation of activity-dependent communication between the presynapse and the nucleus (Ivanova et al, 2015), and the organization of the readily releasable pool of SVs (Butola et al, 2017;Parthier et al, 2018). Piccolo possesses regions of high sequence similarity to Bassoon, another conserved AZ protein.…”
Section: Introductionmentioning
confidence: 99%
“…One of the highly conserved AZ components is the large (Ͼ500 kDa) scaffold protein Piccolo, which organizes various aspects of presynaptic function at chemical synapses (Cases-Langhoff et al, 1996;Wang et al, 1999;Gundelfinger et al, 2016). Among these are functions in AZ assembly during synaptogenesis (Shapira et al, 2003), the dynamic regulation of presynaptic actin (Waites et al, 2011;Wagh et al, 2015), the control of presynaptic proteostasis (Waites et al, 2013;Ivanova et al, 2016), the regulation of activity-dependent communication between the presynapse and the nucleus (Ivanova et al, 2015), and the organization of the readily releasable pool of SVs (Butola et al, 2017;Parthier et al, 2018). Piccolo possesses regions of high sequence similarity to Bassoon, another conserved AZ protein.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin-proteasome system (UPS) modulates the levels of synaptic proteins, such as synaptophysin, syntaxin, Munc1 and Rab3-interacting molecule 1 (RIM1), and Bassoon and Piccolo in the presynaptic active zone [28][29][30][31][32][33]. Yao et al reported that SCRAPPER, an E3 ubiquitin ligase, directly binds to and ubiquitylates RIM1 regulating synaptic vesicle release via RIM1 degradation and proteasome activity in vivo [32].…”
Section: Discussionmentioning
confidence: 99%
“…398relies on ubiquitination. The regulation of presynaptic ubiquitination is likely achieved through the 399 targeted expression of different E2 and E3 ubiquitin ligases(Hallengren et al, 2013) or via 400 presynaptic cytomatrix proteins themselves(Ivanova et al, 2016; Waites et al, 2013). This raises 401 the yet unexplored possibility that presynaptic structural dynamics and UPS activity are tightly 402linked.…”
mentioning
confidence: 99%